High relevance of invasive fungal disease in chronic liver transplant failure: a comprehensive cross-sectional study - Puzalkova, Aleksandra; Hofmann, Katharina; Pfeffer, Tilman; Klein, Isabel M.; Mehrabi, Arianeb; Merle, Uta; Stenzinger, Albrecht; Penzel, Roland; Flechtenmacher, Christa; Schirmacher, Peter (Virchows Archiv, 2025)
Invasive fungal infection (IFI) is a severe complication in organ transplant patients and a major diagnostic and therapeutic challenge. The aim of this comprehensive retrospective study was the characterization of IFI in context of chronic liver transplant failure regarding prevalence, morphological changes, and inducing fungal species. All explanted liver transplants due to chronic transplant failure from Heidelberg University Hospital were extensively reexamined for the presence of mycotic infection. Special stains were performed to uncover severity and associated conditions of IFI and fungal species were identified on the molecular level. Light-microscopic examination revealed fungal infection in 41 (27.5%) of 149 explanted livers with chronic transplant failure, with 68% representing newly specified cases compared to primary reports. We could show an increase of the proportion of mycotic infections during the investigated time period (1991-2021) as well as a shorter transplant survival when compared to the non-affected organs. Typically, large bile ducts were affected, accompanied by acute inflammation with frequent abscess and bile concrement formation. In 35 of 41 cases, the identification of the fungal species was achieved, revealing Candida albicans as prominent species (74.3%). In three autopsy livers of patients that died after liver transplantation of septic multiorgan failure, Candida spp. could be identified. Our data show the underestimated prevalence and high diagnostic and clinical relevance of mycotic infection in chronic liver transplant failure. Adapting diagnostic procedures, molecular pathological analyses, and therapeutic strategies is relevant to identify and prevent chronic transplant organ failure caused by IFIs.